The Influence of Online Learning, Study Motivation, and Self-directed Learning on Students’ Learning Interest - Patriya, Eka; Handayani; Harmadi, Ashur; Purnamasari, Wuri; Kusumawati, Reni Diah (Archives of Business Research, 2024)
The shift in the educational paradigm towards online learning which is increasingly dominant in the current digital era requires a deeper understanding of its impact on students’ interest in learning. Along with that, students’ internal factors such as motivation and level of self-directed learning play an important role in creating an effective learning environment. A deeper understanding of the interaction between online learning, study motivation, self-directed learning and student interest in learning is essential in efforts to improve the quality of learning in today’s digital environment. This research aims to determine the influence of online learning, study motivation, and self-directed learning on students’ interest in learning. Through collecting data from a sample of students, statistical analysis methods are used to understand the relationship between these variables. The research results show that online learning has a significant influence on students’ interest in learning. In addition, study motivation and self-directed learning are also positively related to students’ interest in learning. The implications of these findings provide important insights for the development of more effective online learning strategies and increasing student motivation and self-directed learning in digital learning environments.